(untitled) (Journal of Computational Mathematics, 1999)
In this paper, the phenomena of spirals are numerically presented by MmB scheme [1] for initial value problems of 2-D gas dynamics (γ=1.4), which include 2-D Riemann problems and continuous initial value problems. The numerical results are well coincide with on the exact solution in [2] and the conjectures on solution structure in [3] for 2-D isentropic and adiabatic flows. In isentropic flow, for high speed rotation (v_0/c_0 >2), there is a region of vacuum at the origin and for low speed rotation (v_0/c_0